THE INFLUENCE OF INTEREST AND MOTIVATION ON COLLEGE STUDENTS’ LANGUAGE AND ART APPRECIATION LEARNING OUTCOMES - Triarisanti, Risa; Purnawarman, Pupung (UPI Press, 2019)
A good and appropriate learning process will motivate learners, and will eventually have an impact on improved learning outcomes. The researchers conducted an investigation into the influence of interest and motivation on learning outcomes of Korean Education Study Program students in a state university in Indonesia in the particular subject of Language and Art Appreciation. The compulsory subject is part of the faculty’s mission to cultivate literary and art appreciation of its students. A survey employing a Likert-based questionnaire consisting of 60 items was carried out, and documentary analysis was conducted to the students’ final exam grades in the subject of Language and Art Appreciation. The results show that interest and motivation had significant influence on students’ learning outcomes, as shown by their final exam grades in the subject. It can be concluded then that high level of interest and motivation determined the success of learning outcomes, especially in the subject of Language and Art Appreciation.